The description of community participation in development - Fahik, Yakobus; Mbiri, Adeodata Laniria Charla Barros; Seran, Remigius (The International Journal of Politics and Sociology Research, 2024)
The research focuses on community participation in the implementation of the work program in Teba Village: whether the work program implemented is the result of a decision-making process or the village head's initiative. Using Arnstein's participation ladder, we will describe the level of community participation in development in Teba Village, Biboki Tan Pah District, Timor Tengah Utara Regency. The data was collected using the interview method and supported by documents like village meeting minutes, meeting attendance lists, and work plan documents from 2019-2024. The data analyzed is to determine the level of community participation. We found that community participation in Teba village was at the second level. At the information provision rung, the public is getting information, but a decision already took.  In the consultation rung, the village head holds discussion forums but does not have a guarantee the village government accept the suggestion. In placation rung, the government makes promises but is easy to ignore.